Case Report: endoscopic microvascular decompression for trigeminal neuralgia in a centenarian: a landmark case with 5-year follow-up - Fang, Xuhao; Tang, Feng; Deng, Yao; Zhou, Yue; Gu, Weidong; Mao, Renling (Frontiers in Surgery, 2025)
BackgroundEndoscopic Microvascular Decompression (E-MVD) is a well-established effective treatment option for trigeminal neuralgia (TN). However, its application in ultra-elderly patients, particularly centenarians, has never been documented.Case DescriptionA centenarian with TN for five years presented to our hospital in January 2020. Her symptoms had progressively worsened over the preceding three months. Despite extreme age, her organ function remained relatively preserved based on comprehensive physical and laboratory examinations. E-MVD was performed, and the patient experienced immediate pain relief without any neurological dysfunction. During five years of follow-up, there was no recurrence of symptoms; the patient remains symptom-free at 105 years of age.ConclusionThis case study presents the successful use of E-MVD in a centenarian patient suffering from TN, highlighting its potential as a viable treatment option even in this advanced age group. Further studies are needed to confirm these findings and explore the generalizability of this approach.